(untitled) (Historia, 2021)
One of the aims of Johannesburg’s British controlled town council after the South African War (1899-1902) was to provide open public leisure spaces for its white citizens. The establishment and development of Ellis Park as a major sport centre wasone of these endeavours. In 1908 the council bought disused land in New Doornfontein, taking the first step towards achieving this grand vision, namely the construction of a swimming bath that met all the requirements for an international tournament. The First World War interrupted any further development but the 1920s witnessed impressive expansion to include tennis courts, cricket pitches and rugby football grounds. By the end of the 1920s the council and the Transvaal Rugby Football Union that was a key stakeholder in the development, could proudly claim that they had achieved their dream of establishing an international sports arena for Johannesburg. Ellis Park became a significant urban marker, a symbol of prestige for the fast growing city as well as in the transformation of Johannesburg’s urban fabric into a modern city.